UPGRADE MANAJEMEN USAHA PRODUK BATU BATA PADA ERA PANDEMI COVID-19 - Rulyanti Susi Wardhani; Julia Julia; Duwi Agustina; Anggraeni Yunita (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this service activity is to empower a group of target communities to become independent communities. After empowerment is carried out through appropriate technology produced and training activities for 8 (eight) months for the Brick Business partner Mr. Zulkiflide detail the output targets are as follows: a) Management improvement. Indicators of the success of PKM activities in the form of improving management of partners, namely: the implementation of neat and good business financial reports on a continuous basis, as well as the application of marketing strategies to businesses. b) increased knowledge of product marketing strategies. Indicators of the success of PKM activities in the form of increasing knowledge about product marketing strategies to partners, namely: 100% e-commerce application and continuous stone stock calculation applications, c) increasing knowledge about business capital/bank credit. Indicators of increasing knowledge about business capital/bank credit to partners, namely: understanding in making bank credit proposals. The working procedures in this PKM are as follows: Stage of Making Appropriate Technology for e-commerce web and brick stock calculation applications, Training stages, namely: Business Management Training (Training on making and presenting financial reports and marketing training strategies), training on the use of e-commerce and the application of the calculation of the stock of bricks, training in capital management for micro-enterprises and a simulation of making bank loan proposals, and the PKM evaluation stage. The results of this PKM can increase the competitiveness of partners' businesses; the application of science and technology by 60%; and an increase in knowledge and skills by 70%.